2014
DOI: 10.1021/nl500946u
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ultrathin Nanowires Using Superfluid Helium Droplets

Abstract: Direct preparation of long one-dimensional (1D) nanostructures with diameters <10 nm inside superfluid helium droplets is reported. Unlike conventional chemical synthetic techniques, where stabilizers, templates, or external fields are often required to induce 1D growth, here, we exploit the use of quantized vortices to guide the formation of ultrathin nanowires. A variety of elements have been added to the droplets to demonstrate that this is a general phenomenon, including Ni, Cr, Au, and Si. Control of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 50 publications
4
72
0
Order By: Relevance
“…1,6,8,10,12 There is also a close analogy between our observations and the results of the experiments involving superfluid He microdroplets. [14][15][16] It was argued that in bulk superfluid He and in He microdroplets the nanowires are formed due to the trapping of the impurity atoms at the cores of quantized vortices. Most likely, quantized vortices are also present in our sample cell under the typical experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6,8,10,12 There is also a close analogy between our observations and the results of the experiments involving superfluid He microdroplets. [14][15][16] It was argued that in bulk superfluid He and in He microdroplets the nanowires are formed due to the trapping of the impurity atoms at the cores of quantized vortices. Most likely, quantized vortices are also present in our sample cell under the typical experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore suggested that in superfluid He both, hydrogen filaments 3,5 and metallic nanowires 6,7 are formed due to the aggregation of dopants trapped at the vortex core. Currently, most publications on this quickly growing field of research support that interpretation, 10,[14][15][16]20 both for bulk superfluid He and for He microdroplets. The interest in this phenomenon is twofold.…”
Section: Introductionmentioning
confidence: 90%
“…Upon impact, the helium atoms evaporate while the Ag atoms remain on the surface keeping their "in situ" cluster structure, revealing a filamentlike distribution corresponding to the vortex line they were originally attached to inside the droplet. Experiments for other atomic impurities have been recently conducted, where the presence of vortex lines in helium droplets has been exploited to guide the formation of ultrathin nanowires [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In previous experiments no elongated nanoparticles have been observed in helium droplets composed of <10 6 helium atoms, [31][32][33] suggesting that quantized vortices, even if they exist, do not have significant influence on the clustering of H2TPyP and Au in this work. Therefore, the formation of Au-H2TPyP complexes is presumably driven by intermolecular forces.…”
Section: H2tpyp/au Complexesmentioning
confidence: 39%